Construction waste mud cake based non-burned cement brick and preparation method thereof

CN122770116APending Publication Date: 2026-09-18SINOHYDRO BUREAU 1 CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610949512.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

然而,在施工废弃泥饼掺量较高且泥饼不经干化处理的情况下,泥饼与水泥、集料之间的拌和顺序、分散状态、成型密实性以及养生条件均会对免烧水泥砖的力学性能产生影响

Benefits of technology

[0029] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention uses construction waste mud cake, cement, and fine aggregate as raw materials to prepare non-fired cement bricks. Construction waste mud cake generated by the aggregate processing system can be directly used in building material preparation, reducing pretreatment steps such as drying, calcination, and grinding, and lowering the processing flow and disposal costs of mud cake resource utilization. This invention first mixes construction waste mud cake with cement, then adds fine aggregate and continues mixing, allowing cement to preferentially disperse in the mud cake particle system and form a cementing effect with the moisture in the mud cake. The fine aggregate, as skeleton particles, participates in molding, and the cementitious phase formed by the mud cake and cement fills the spaces between the fine aggregates, which helps improve the uniformity of the mixture and the stability of the molded structure. This invention uses vibration compaction and room temperature curing, allowing the molded body to complete cement hydration and strength development under a relatively stable particle contact state, which is beneficial for improving the molding density and compressive strength stability of the non-fired cement bricks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122770116A_ABST
    Figure CN122770116A_ABST
Patent Text Reader

Abstract

The application belongs to the field of solid waste resource utilization, and provides a construction waste mud cake-based non-burning cement brick and a preparation method thereof. The non-burning cement brick comprises construction waste mud cake, cement and fine aggregate; in the preparation, the construction waste mud cake is first mixed with the cement, then the fine aggregate is added for continuous mixing, and the construction waste mud cake-based non-burning cement brick is obtained through vibration compaction forming, demolding and room temperature curing. The application can realize the building material utilization of the construction waste mud cake without drying and calcining treatment, and can improve the structure stability of the formed body through the mixing sequence and the curing mode, so that the obtained non-burning cement brick has good compressive performance and engineering application adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste resource utilization, and relates to a construction waste mud cake-based non-fired cement brick and its preparation method. Background Technology

[0002] During operation, aggregate processing systems generate a large amount of construction waste mud cake. Current methods for utilizing construction waste mud cake and similar clay-like solid waste in building materials mainly include using it as cement concrete admixtures, geopolymer raw materials, sintered brick raw materials, ceramsite raw materials, or non-fired brick raw materials. Among these, drying and grinding or calcination and grinding are common pretreatment methods. These processes can improve the dispersion and reactivity of the mud cake, but they typically require a long processing cycle and involve high energy consumption and equipment investment, making it unsuitable for on-site disposal and low-cost resource utilization. For construction waste mud cake in a moist state, if it is used directly in building material preparation without drying, grinding, or calcination, the moisture content, fine particle agglomeration, and mixing uniformity with cementitious materials will affect the density and strength stability of the molded material.

[0003] Non-fired cement bricks are characterized by relatively simple processing, no need for sintering, and suitability for the resource utilization of solid waste, making them one direction for the utilization of construction waste mud cakes as building materials. By combining construction waste mud cakes, cement, and aggregates, cement can form a cementitious phase, and aggregates can form a skeletal structure, thereby producing non-fired cement bricks with certain compressive strength. However, when the amount of construction waste mud cake is high and the mud cake is not dried, the mixing sequence, dispersion state, molding density, and curing conditions between the mud cake, cement, and aggregates will all affect the mechanical properties of the non-fired cement bricks.

[0004] In particular, conventional cement products typically rely on high humidity for curing to promote cement hydration. However, in high-volume construction waste mud cake systems, the mud cake particles themselves contain water and exhibit fine particle aggregation characteristics. High humidity conditions may alter the contact state between mud cake particles, affecting the internal structural stability of the molded body. Furthermore, if cement is not sufficiently dispersed within the mud cake system during mixing, it can easily lead to insufficient localized bonding, impacting the compressive strength and strength uniformity of the resulting non-fired cement bricks.

[0005] Therefore, in the existing process of utilizing construction waste mud cakes as building materials, there is still a problem that when undried construction waste mud cakes are directly used to prepare non-fired cement bricks, the water content, mixing and dispersion state, and curing conditions of the mud cakes can easily affect the density and compressive strength stability of the molded body. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a construction waste mud cake-based non-fired cement brick and its preparation method, thereby meeting the needs of actual production.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a construction waste mud cake-based non-fired cement brick, the construction waste mud cake-based non-fired cement brick comprising construction waste mud cake, cement and fine aggregate;

[0009] The construction waste mud cake is the construction waste mud cake generated by the sand and gravel aggregate processing system.

[0010] The construction waste mud cake, cement, and fine aggregate are mixed, vibrated, compacted, and cured to form the construction waste mud cake-based non-fired cement brick.

[0011] Preferably, the dosages of the construction waste mud cake, cement, and fine aggregate are as follows: 1100 kg / m³ of construction waste mud cake. 3 Cement 220–385 kg / m³ 3 Fine aggregate 880kg / m 3 .

[0012] Preferably, the cement content is 220 kg / m³. 3 275kg / m 3 330kg / m 3 Or 385kg / m 3 .

[0013] Preferably, the construction waste mud cake has a moisture content of 25-35% and a pH value of 8-10.

[0014] Preferably, the cement is PO 42.5 grade cement.

[0015] Preferably, the fine aggregate is fine aggregate produced by a sand and gravel processing system, and the particle size of the fine aggregate is 5mm to 10mm.

[0016] Preferably, the converted water-cement ratio of the construction waste mud cake-based non-fired cement brick is 0.85–1.50.

[0017] In a second aspect, the present invention provides a method for preparing non-fired cement bricks based on construction waste mud cake as described in the first aspect, the method comprising the following steps:

[0018] S1, mix the construction waste mud cake with cement to obtain the first mixture;

[0019] S2, add fine aggregate to the first mixture and continue mixing to obtain the second mixture;

[0020] S3, the second mixture is loaded into the mold and vibrated to compact it, thus obtaining the molded body;

[0021] S4. After demolding the molded body, it is cured at room temperature to obtain construction waste mud cake-based non-fired cement bricks.

[0022] Preferably, in S1, the mixing time is 120s to 180s; in S2, the mixing time continues for 120s to 180s.

[0023] Preferably, in step S3, the mold has a size of 100 mm × 100 mm × 100 mm; in step S4, the molded body is demolded 24 hours after molding.

[0024] Construction waste mud cake contains a large number of fine particles and a certain amount of moisture, and these particles tend to agglomerate in their original state. When construction waste mud cake is mixed directly with cement, cement particles can enter the gaps between the mud cake particles and adhere to the surface of the mud cake particles. As mixing proceeds, the moisture in the mud cake comes into contact with the cement, and the cement begins to undergo a hydration reaction, forming hydration products mainly composed of hydrated calcium silicate gel, hydrated aluminate products, and calcium hydroxide. These hydration products are distributed between the mud cake particles, transforming the mud cake particles from a simple physical aggregate state to a particle-bonded state with a cementing effect.

[0025] This invention first mixes construction waste mud cake with cement, then adds fine aggregate and continues mixing. This mixing sequence ensures that the cement preferentially contacts the mud cake, reducing the possibility of the cement being partially encapsulated or unevenly dispersed by the fine aggregate. This allows the cement to first form a relatively continuous cementitious phase around the mud cake particles. When the fine aggregate is subsequently added, it acts as a skeleton particle distributed throughout the mud cake-cement mixture. The cementitious phase formed by the mud cake and cement fills the spaces between the fine aggregates and forms a bonding interface on the surface of the fine aggregates, thus creating a molded structure composed of a fine aggregate skeleton, a mud cake filling phase, and a cement hydration cementitious phase.

[0026] During vibration compaction, the particles in the second mixture rearrange, reducing interparticle porosity and increasing the contact area between the mud cake, cement, and fine aggregate. Vibration makes it easier for the fine particles in the mud cake to fill the voids between the fine aggregate, while simultaneously allowing cement particles and hydration products to form a bonding structure in the particle contact area. After demolding, the molded body continues to cure, gradually increasing the amount of cement hydration products and strengthening the bonding between mud cake particles and between the mud cake and fine aggregate, thus forming a construction waste mud cake-based non-fired cement brick with a certain compressive strength.

[0027] This invention employs a room temperature curing method, which is more suitable for high-volume construction waste mud cake systems compared to high-humidity standard curing. In this system, the mud cake itself contains a certain amount of moisture, providing a source of hydration for early cement hydration. If the curing environment is too humid, the contact state between mud cake particles is easily affected by additional moisture, weakening interparticle friction and cohesion, and reducing the internal structural stability of the molded body. Under room temperature curing conditions, moisture migration and cement hydration within the molded body can occur under relatively stable mud cake particle contact conditions, which is beneficial for maintaining the skeleton-filler-cement structure formed after compaction.

[0028] The cement content directly affects the compressive strength of non-fired cement bricks based on construction waste mud cake. At lower cement contents, the cementitious phase formed between mud cake particles and fine aggregates is insufficient, resulting in limited bonding strength in the particle contact area. With increasing cement content, the amount of hydration products increases, enhancing the bonding between mud cake particles, between mud cake and fine aggregates, and in the contact area with fine aggregates. This leads to a more complete continuous cemented structure within the molded body, thereby increasing the compressive strength. Previous experimental results also indicate that, under fixed conditions of construction waste mud cake and fine aggregate content, increasing the cement content improves the overall compressive strength of non-fired cement bricks based on construction waste mud cake.

[0029] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention uses construction waste mud cake, cement, and fine aggregate as raw materials to prepare non-fired cement bricks. Construction waste mud cake generated by the aggregate processing system can be directly used in building material preparation, reducing pretreatment steps such as drying, calcination, and grinding, and lowering the processing flow and disposal costs of mud cake resource utilization. This invention first mixes construction waste mud cake with cement, then adds fine aggregate and continues mixing, allowing cement to preferentially disperse in the mud cake particle system and form a cementing effect with the moisture in the mud cake. The fine aggregate, as skeleton particles, participates in molding, and the cementitious phase formed by the mud cake and cement fills the spaces between the fine aggregates, which helps improve the uniformity of the mixture and the stability of the molded structure. This invention uses vibration compaction and room temperature curing, allowing the molded body to complete cement hydration and strength development under a relatively stable particle contact state, which is beneficial for improving the molding density and compressive strength stability of the non-fired cement bricks. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the process for preparing non-fired cement bricks based on construction waste mud cake according to the present invention.

[0031] Figure 2 This is a comparison chart of compressive strength over 7 days of standard health maintenance.

[0032] Figure 3 A comparison chart of compressive strength after 28 days of standard health maintenance;

[0033] Figure 4 Comparison chart of compressive strength after 7 days of room temperature conditioning;

[0034] Figure 5 Comparison chart of compressive strength after 28 days of room temperature conditioning;

[0035] Figure 6 This is a comparison chart of the 7-day compressive strength of the first process;

[0036] Figure 7 This is a comparison chart of the compressive strength of the first process at 28 days.

[0037] Figure 8 This is a comparison chart of the 7-day compressive strength of the second process;

[0038] Figure 9 This is a comparison chart of the compressive strength of the second process after 28 days. Detailed Implementation

[0039] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.

[0040] To ensure consistency with the original experimental records, the figures and some test results are numbered "1-1, 1-2, 1-3, 1-4". "1-1" corresponds to Example 1, "1-2" to Example 2, "1-3" to Example 3, and "1-4" to Example 4. These numbers are only used to distinguish test groups under different cement content conditions and do not affect the understanding of the embodiment numbers and technical solutions of this invention.

[0041] The mud cake used in this invention comes from a sand and gravel aggregate processing system and is gray mud-like. After testing, the concentrations of cadmium, mercury, lead, chromium, arsenic, nickel, zinc, copper and their compounds, as well as mineral oil in the mud cake all meet the pollutant concentration limits for Class B sludge products in Table 1 of GB 4284-2018 "Standard for Pollutant Control of Agricultural Sludge".

[0042] The cement used in this invention is PO 42.5 grade produced by Southern Cement.

[0043] In embodiments 1-4 of this invention, the proportions of construction waste mud cake, fine aggregate and cement are shown in Table 1.

[0044] Table 1. Raw material mix proportions for construction waste mud cake-based non-fired cement bricks

[0045]

[0046] Example 1

[0047] This embodiment provides a construction waste mud cake-based non-fired cement brick and its preparation method. The preparation method specifically includes the following steps:

[0048] S1, based on 1100 kg / m³ of construction waste mud cake. 3 220kg / m³ of cement 3 The construction waste mud cake and cement were weighed according to the mixing ratio. The weighed construction waste mud cake and cement were added to a horizontal mixer and mixed for 150 seconds to obtain the first mixture. The construction waste mud cake came from the sand and gravel aggregate processing system, with a moisture content of 30.3% and a pH value of 9.0. The cement was PO 42.5 grade cement.

[0049] S2, based on fine aggregate 880kg / m³ 3 Weigh out the fine aggregate according to the mixing ratio, add the weighed fine aggregate to the first mixture, and continue stirring for 150 seconds to obtain the second mixture; wherein, the fine aggregate is fine aggregate produced by the sand and gravel processing system, with a particle size of 5mm to 10mm; the converted water-cement ratio in this embodiment is 1.50;

[0050] S3, the second mixture is loaded into a 100mm×100mm×100mm standard mold and compacted by vibration table to obtain the molded body;

[0051] S4. After molding the molded body for 24 hours, demold it and cure it at room temperature to obtain construction waste mud cake-based non-fired cement bricks.

[0052] Example 2

[0053] This embodiment provides a construction waste mud cake-based non-fired cement brick and its preparation method. The preparation method specifically includes the following steps:

[0054] S1, based on 1100 kg / m³ of construction waste mud cake. 3 Cement 275kg / m 3 The construction waste mud cake and cement were weighed according to the mixing ratio. The weighed construction waste mud cake and cement were added to a horizontal mixer and mixed for 150 seconds to obtain the first mixture. The construction waste mud cake came from the sand and gravel aggregate processing system, with a moisture content of 30.3% and a pH value of 9.0. The cement was PO 42.5 grade cement.

[0055] S2, based on fine aggregate 880kg / m³ 3Weigh out the fine aggregate according to the mixing ratio, add the weighed fine aggregate to the first mixture, and continue stirring for 150 seconds to obtain the second mixture; wherein, the fine aggregate is fine aggregate produced by the sand and gravel processing system, with a particle size of 5mm to 10mm; the converted water-cement ratio in this embodiment is 1.20;

[0056] S3, the second mixture is loaded into a 100mm×100mm×100mm standard mold and compacted by vibration table to obtain the molded body;

[0057] S4. After molding the molded body for 24 hours, demold it and cure it at room temperature to obtain construction waste mud cake-based non-fired cement bricks.

[0058] Example 3

[0059] This embodiment provides a construction waste mud cake-based non-fired cement brick and its preparation method. The preparation method specifically includes the following steps:

[0060] S1, based on 1100 kg / m³ of construction waste mud cake. 3 330kg / m³ of cement 3 The construction waste mud cake and cement were weighed according to the mixing ratio. The weighed construction waste mud cake and cement were added to a horizontal mixer and mixed for 150 seconds to obtain the first mixture. The construction waste mud cake came from the sand and gravel aggregate processing system, with a moisture content of 30.3% and a pH value of 9.0. The cement was PO 42.5 grade cement.

[0061] S2, based on fine aggregate 880kg / m³ 3 Weigh out the fine aggregate according to the mixing ratio, add the weighed fine aggregate to the first mixture, and continue stirring for 150 seconds to obtain the second mixture; wherein, the fine aggregate is fine aggregate produced by the sand and gravel processing system, with a particle size of 5mm to 10mm; the converted water-cement ratio in this embodiment is 1.00;

[0062] S3, the second mixture is loaded into a 100mm×100mm×100mm standard mold and compacted by vibration table to obtain the molded body;

[0063] S4. After molding the molded body for 24 hours, demold it and cure it at room temperature to obtain construction waste mud cake-based non-fired cement bricks.

[0064] Example 4

[0065] This embodiment provides a construction waste mud cake-based non-fired cement brick and its preparation method. The preparation method specifically includes the following steps:

[0066] S1, based on 1100 kg / m³ of construction waste mud cake. 3 Cement 385kg / m3 The construction waste mud cake and cement were weighed according to the mixing ratio. The weighed construction waste mud cake and cement were added to a horizontal mixer and mixed for 150 seconds to obtain the first mixture. The construction waste mud cake came from the sand and gravel aggregate processing system, with a moisture content of 30.3% and a pH value of 9.0. The cement was PO 42.5 grade cement.

[0067] S2, based on fine aggregate 880kg / m³ 3 Weigh out the fine aggregate according to the mixing ratio, add the weighed fine aggregate to the first mixture, and continue stirring for 150 seconds to obtain the second mixture; wherein, the fine aggregate is fine aggregate produced by the sand and gravel processing system, with a particle size of 5mm to 10mm; the converted water-cement ratio in this embodiment is 0.85;

[0068] S3, the second mixture is loaded into a 100mm×100mm×100mm standard mold and compacted by vibration table to obtain the molded body;

[0069] S4. After molding the molded body for 24 hours, demold it and cure it at room temperature to obtain construction waste mud cake-based non-fired cement bricks.

[0070] Equipment and mixing method:

[0071] This invention utilizes a horizontal mixer combined with a vibrating table for compaction of cement brick specimens. Two mixing processes were employed to analyze the impact of different preparation methods on the mechanical properties of mud cake-based cement bricks. For the first mixing process: First, weighed waste mud cake and fine aggregate were poured into the horizontal mixer and mixed for 150 seconds. Then, weighed cement was added to the mixer and mixed for another 150 seconds. For the second mixing process: First, weighed mud cake and cement were uniformly poured into the horizontal mixer and mixed for 150 seconds. Then, weighed fine aggregate was added to the mixer and mixed for another 150 seconds. After uniform mixing, the mixture was placed into a 100×100×100mm standard mold and compacted using a vibrating table. After 24 hours of molding, the bricks were demolded and subjected to room temperature curing and standard curing (temperature: 20±5℃, humidity: 90±5%). Compressive strength tests were conducted after 7 days and 28 days of conditioning, with three parallel tests performed for each group.

[0072] Compressive strength test:

[0073] According to the standard GB / T 4111-2013 "Test Methods for Concrete Blocks and Bricks", this test uses a universal testing machine to test the compressive strength of cement bricks. Loading is controlled by test force, with a loading rate of 3 kN / s. The test procedure for mud-cake-based cement bricks is as follows: Figure 1 As shown.

[0074] Compressive strength analysis of mud cake-based cement bricks:

[0075] (1) Compressive strength results:

[0076] The compressive strength results of mud cake-based cement bricks at 7 days and 28 days under different cement dosages, mixing processes, and curing conditions are shown in Tables 2 and 3, respectively. The results show that the compressive strength of mud cake-based cement bricks increases significantly with increasing curing age. Furthermore, mixing process, curing conditions, and cement dosage all significantly affect the compressive strength of mud cake-based cement bricks.

[0077] Table 2. Compressive strength results of mud cake-based cement bricks using the first mixing process.

[0078]

[0079] Table 3. Compressive strength results of mud cake-based cement bricks using the second mixing process.

[0080]

[0081] (2) The effect of mixing process on compressive strength:

[0082] The compressive strength of cement bricks under different mixing processes is as follows: Figures 2-5 As shown in the figure. According to the results, except for test groups 1-3, the compressive strength of cement bricks from the second process was higher than that from the first mixing process. After standard curing for 28 days, the compressive strength of cement bricks from groups 1-1, 1-2, and 1-4 of the second mixing process was 7.54%, 19.00%, and 8.50% higher than that of the first process, respectively. After room temperature curing for 28 days, the compressive strength of cement bricks from each group of the second mixing process was 7.10%, 9.62%, and 4.76% higher than that of the first process, respectively. This is because the second mixing process first thoroughly mixes the cement and mud cake. Due to the presence of cement, the mixture already has a certain cementitious capacity. Then, mixing it with fine aggregate promotes uniform mixing between the cementitious material and the fine aggregate, thereby significantly improving the dispersion of cement particles in the mixture. The second mixing process, groups 1-3, showed lower compressive strengths than adjacent cement content groups, indicating that the compactness of the high-cement-content cake system is still affected by mixing uniformity and vibration compaction. Therefore, this invention uses the overall trend of multiple cement content groups under different curing conditions as the basis for performance evaluation. The results show that the second mixing process can improve the compressive strength of the clay cake-based cement bricks under most test conditions, indicating that mixing the clay cake with cement first and then adding fine aggregates is beneficial for improving the dispersion state of the mixture and its mechanical properties after molding.

[0083] (3) The influence of health conditions on compressive strength

[0084] The compressive strengths of cement bricks at 7 days and 28 days under different curing conditions are as follows: Figures 6-9 As shown in the figure. The results indicate that, for any preparation process, the compressive strength of cement bricks cured at room temperature is significantly higher than that cured under standard conditions. Under the first mixing process, the 28-day compressive strength of cement bricks in groups 1-1, 1-2, 1-3, and 1-4 cured at room temperature was 139.90%, 42.25%, 47.57%, and 50.17% higher than that under standard curing conditions, respectively. Under the second mixing process, the 28-day compressive strength of cement bricks in each group cured at room temperature was 138.91%, 31.03%, 18.55%, and 44.99% higher than that under standard curing conditions, respectively. Approximately 50% of the cement bricks prepared in this study are composed of mud cake. From a microscopic perspective, changes in humidity alter the interaction between mud cake particles. As humidity increases, the contact between mud cake particles gradually loosens, and friction and cohesion gradually decrease, thereby weakening the mud cake's resistance to deformation and consequently reducing the compressive strength of the cement bricks. Therefore, in the subsequent production process, room temperature curing should be used to maintain cement bricks.

[0085] (4) The effect of cement admixture on compressive strength

[0086] The results show that, except for groups 1-3 in the second mixing process which were affected by fluctuations in specimen compaction, the overall compressive strength of mud cake-based cement bricks increased with increasing cement content. Using the first mixing process, when the cement content increased from 220 kg / m³, the compressive strength of the bricks increased. 3 Increased to 385 kg / m 3 At that time, the 7-day compressive strength of cement bricks increased by 153.84% and 84.07% under standard curing and room temperature curing, respectively, and the 28-day compressive strength increased by 189.05% and 80.93%, respectively. Through the second mixing process, when the cement dosage increased from 220 kg / m³, the... 3 Increased to 385 kg / m 3 At that time, the 7-day compressive strength of cement bricks increased by 170.37% and 78.91% under standard curing and room temperature curing, respectively, and the 28-day compressive strength increased by 191.63% and 76.99%, respectively. Increasing the cement content can enhance the consolidation between the mud cake particles and fine aggregates, thereby increasing the compressive strength of the cement bricks. Based on the compressive strength results, it can be seen that when the cement content is 385 kg / m³... 3 At that time, the 28-day strength of cement bricks cured at room temperature can meet the requirements of MU15 strength grade, and the 7-day strength can meet the requirements of MU10 strength grade.

[0087] Based on the above results, it can be seen that the cement content significantly affects the compressive strength of cement bricks. In order to further quantify the influence of cement content on the mechanical properties of cement bricks, this study systematically evaluates the significance of the influence of different cement contents through one-way ANOVA. The calculation formulas for one-way ANOVA are shown in equations (1) to (6) below.

[0088]

[0089] Where k is the number of levels of the factor; n i x is the sample size of the i-th group; N is the total sample size; x ij This refers to the j-th observation in the i-th group; Let be the sample mean of the i-th group; SST is the total sample mean; SSA is the sample total sum of squares; SSE is the between-group sum of squares; MAS is the between-group mean square; MSE is the within-group mean square; F is the statistic.

[0090] The experimental data used in this invention are normally distributed, and the experimental results are independent of each other, conforming to the assumptions of analysis of variance. The confidence levels for the analysis of variance were set at 0.05 and 0.01, respectively. The degrees of freedom for SST were 11, for SSE 8, and for SSA 3. The calculation results of the one-way ANOVA are shown in Table 4 below. According to the results, under any preparation process and curing conditions, the F-value of the compressive strength of cement bricks is much greater than F0. crit-0.05 With F crit-0.01 This indicates that the cement content has a significant impact on the compressive strength of cement bricks. Therefore, the cement content is an important process parameter affecting the mechanical properties of non-fired cement bricks based on construction waste mud cake.

[0091] Table 4. Results of one-way ANOVA on the effect of cement content on the mechanical properties of cement bricks

[0092]

[0093] Analysis of production capacity and cost of mud cake-based cement bricks:

[0094] Cement brick production capacity analysis:

[0095] (1) Standard brick production capacity: It is proposed to use the Jiageng 3-15 small fully automatic brick machine for cement brick production. Its main power is 18kW, the main machine weight is 4.5 tons, the vibration frequency is 4600 times / minute, the excitation force is 22kN, and the standard brick forming cycle is 13s~15s. Considering pallet replacement, raw material mixing and mechanical operation, based on 2 pallets per minute, 22 cement bricks per pallet, and 10 hours of production per day, 26400 cement bricks can be produced per day, consuming 19.13 m³ of mud cake. 3 The production capacity analysis of standard cement bricks is shown in Table 5 below.

[0096] Table 5. Production Capacity Analysis of Standard Cement Bricks

[0097] parameter 13~15 2640 26400 19.13

[0098] (2) Hollow brick production capacity: The hollow brick forming cycle is 13 s~15 s. Considering pallet replacement, raw material mixing and mechanical operation, based on 2 pallets per minute, 3 hollow cement bricks per pallet, and 10 hours of production per day, 3600 hollow cement bricks can be produced per day, consuming 30.41 m³ of mud cake. 3 The production capacity analysis of hollow cement bricks is shown in Table 6 below.

[0099] Table 6. Production Capacity Analysis of Hollow Cement Bricks

[0100] parameter 13~15 360 3600 30.41

[0101] Cement brick cost analysis:

[0102] (1) Cost analysis of standard bricks

[0103] The standard brick dimensions are 240×115×53mm. 3.22kg of material is required.

[0104] 1) Cement cost: Each standard brick requires 0.32kg~0.56kg of cement (different mix ratios). With the cement price at 300 yuan / ton, the cement cost is approximately 0.096~0.168 yuan / brick.

[0105] 2) Aggregate cost: Each standard brick requires 1.29 kg of fine aggregate. The unit price of fine aggregate is about 37 yuan / ton, and the cost of fine aggregate is about 0.05 yuan / brick.

[0106] 3) Electricity cost: The main power of the brick making machine is 18kW, and the electricity cost is 14 yuan per hour, with an electricity cost of about 0.005 yuan per brick.

[0107] 4) Labor: 4 general laborers are needed, with a total labor cost of 80 yuan / hour. The labor cost is approximately 0.03 yuan / piece.

[0108] 5) Machinery rental cost: One forklift and one small loader are required. The total machinery rental fee is 200 yuan / hour, and the machinery rental cost is approximately 0.075 yuan / piece.

[0109] Therefore, the cost of a single standard brick is 0.256~0.328 yuan.

[0110] (2) Cost analysis of hollow bricks

[0111] The hollow block has dimensions of 390×190×190mm, a hollow rate of 40%, and requires 18.58kg of material.

[0112] 1) Cement cost: Each hollow brick requires 1.86kg~2.27kg of cement. With the cement price at 300 yuan / ton, the cement cost is approximately 0.558 yuan~0.681 yuan / brick.

[0113] 2) Aggregate cost: Each hollow brick requires 7.43 kg of fine aggregate. The unit price of fine aggregate is about 37 yuan / ton, and the cost of fine aggregate is about 0.275 yuan / brick.

[0114] 3) Electricity cost: The main power of the brick making machine is 18kW, and the electricity cost is 14 yuan per hour, with an electricity cost of approximately 0.039 yuan per brick.

[0115] 4) Labor: 4 general laborers are needed, with a total labor cost of 80 yuan / hour. The labor cost is approximately 0.22 yuan / piece.

[0116] 5) Machinery rental cost: One forklift and one small loader are required. The total machinery rental fee is 200 yuan / hour, and the machinery rental cost is approximately 0.56 yuan / piece.

[0117] Therefore, the cost of a single hollow brick is 1.652~1.775 yuan.

[0118] The cost analysis of standard bricks and hollow bricks is shown in Table 7 below.

[0119] Table 7. Cost Summary of Standard Bricks and Hollow Bricks

[0120] Standard bricks 0.096~0.168 0.05 0.005 0.03 0.075 0.256~0.328 0.38 hollow bricks 0.558~0.681 0.275 0.039 0.22 0.56 1.652~1.775 2.2

[0121] Cost analysis has verified that, under the listed production conditions and cost assumptions, the construction waste mud cake-based non-fired cement bricks prepared by this invention have certain production and application feasibility. Therefore, using construction waste mud cakes to prepare cement bricks can not only reduce the environmental pressure caused by waste mud cake disposal, but also reduce the cost of purchasing building materials, which is in line with the low-carbon development orientation.

[0122] Analysis of the application of mud cake-based cement bricks:

[0123] According to the "General Specification for Masonry Structures" GB 55007-2021, the environmental categories of masonry structures should be divided into the following five types based on climatic conditions and the usage environment of the structure, as shown in Table 8.

[0124] Table 8 Classification of Masonry Structures by Service Environment

[0125] 1 dry environment Dry indoor and outdoor environments; outdoor environments with waterproof protection. 2 humid environment Damp indoor or outdoor environments, including environments in contact with non-erosive soil and water. 3 Freeze-thaw environment Cold and humid environments 4 Chlorine-corroded environment Environments in direct contact with seawater, or salt-saturated gaseous environments in coastal areas. 5 Chemically corrosive environment Environments in which chemical erosion occurs in gaseous, liquid, or solid forms, including environments with erosive soils.

[0126] Based on the environmental categories in Table 8 and considering the climate conditions of Jiande City, Zhejiang Province, the region mainly experiences Class 1 and Class 2 environments. Referring to the "General Code for Masonry Structures" GB 55007-2021, the minimum strength grade of concrete brick load-bearing masonry in Class 1 and Class 2 environments should meet the requirements of Table 9 below. For structures with a safety level of Class I or a design service life greater than 50 years, the minimum strength grade should be increased by at least one grade based on Table 9.

[0127] Table 9 Minimum Strength Grade Requirements for Concrete Bricks in Class I and Class II Environments

[0128] 1 MU15 2 MU20

[0129] The minimum strength grade of infill wall blocks shall meet the following requirements: MU3.5 for interior wall hollow concrete blocks and MU5 for exterior walls.

[0130] According to the strength analysis results, when the cement content is 385 kg / m³ 3 Cement bricks prepared using the second preparation process and room temperature curing conditions can meet the MU15 strength grade requirements, satisfying the requirements for load-bearing concrete brick masonry in Class 1 environments. Under the second mixing process and room temperature curing conditions, cement bricks with other cement admixtures can be used as infill wall blocks with corresponding strength grade requirements based on their compressive strength test results.

[0131] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing non-fired cement bricks based on construction waste mud cake, characterized in that, The preparation method includes the following steps: S1, mix the construction waste mud cake with cement to obtain the first mixture; S2, add fine aggregate to the first mixture and continue mixing to obtain the second mixture; S3, the second mixture is loaded into the mold and vibrated to compact it, thus obtaining the molded body; S4. After demolding the molded body, it is cured at room temperature to obtain construction waste mud cake-based non-fired cement bricks.

2. The method for preparing a construction waste mud cake-based non-fired cement brick according to claim 1, characterized in that, In S1, the mixing time is 120s to 180s; in S2, the mixing time continues for 120s to 180s.

3. The method for preparing a construction waste mud cake-based non-fired cement brick according to claim 1, characterized in that, In step S3, the mold has dimensions of 100 mm × 100 mm × 100 mm; in step S4, the molded body is demolded 24 hours after molding.

4. A construction waste mud cake-based non-fired cement brick prepared by the preparation method according to any one of claims 1-3, characterized in that, The construction waste mud cake-based non-fired cement bricks include construction waste mud cakes, cement, and fine aggregates; The construction waste mud cake is the construction waste mud cake generated by the sand and gravel aggregate processing system. The construction waste mud cake, cement, and fine aggregate are mixed, vibrated, compacted, and cured to form the construction waste mud cake-based non-fired cement brick.

5. The construction waste mud cake-based non-fired cement brick according to claim 4, characterized in that, The dosages of the construction waste mud cake, cement, and fine aggregate are as follows: 1100 kg / m³ of construction waste mud cake. 3 Cement 220–385 kg / m³ 3 Fine aggregate 880kg / m 3 .

6. The construction waste mud cake-based non-fired cement brick according to claim 4, characterized in that, The cement dosage is 220 kg / m³. 3 275kg / m 3 330kg / m 3 Or 385kg / m 3 .

7. The construction waste mud cake-based non-fired cement brick according to claim 4, characterized in that, The construction waste mud cake has a moisture content of 25-35% and a pH value of 8-10.

8. The non-fired cement brick based on construction waste mud cake according to claim 4, characterized in that, The cement is PO42.5 grade cement.

9. A construction waste mud cake-based non-fired cement brick according to claim 4, characterized in that, The fine aggregate is produced by the sand and gravel processing system, and the particle size of the fine aggregate is 5mm to 10mm.

10. A construction waste mud cake-based non-fired cement brick according to claim 4, characterized in that, The converted water-cement ratio of the construction waste mud cake-based non-fired cement bricks is 0.85–1.50.